Experimental Study Of Particulate Fouling In Partially Filled Channel With Open-Cell Metal Foam - Shikh Anuar, Fadhilah; Hooman, Kamel; Malayeri, Mohammad Reza; Ashtiani Abdi, Iman (Elsevier Inc., 2020)
This study experimentally investigates particle transport and deposition processes in a partially filled channel with an open-cell metal foam. Various blockage ratio (a ratio of foam height and channel height) in range of 0.05–0.39, and pore density (10 and 30 PPI) were used to determine the effects of the foam microstructure and exterior shape on the propensity of particulate fouling. In-situ observations were conducted using a high-speed camera to determine the particle trajectory and velocity in the partially filled channel. Result shows a complex transport and deposition process, which is significantly influenced by the particle size and pore diameter. If merely considering the exterior shape of the foam, a higher blockage ratio causes more deposition in the upstream region. While, a low blockage ratio causes more deposition on the top surface of the foam block, regardless of pore density. These results demonstrate that the foam arrangement and heights play primary roles in influencing the preferential deposition areas, which is originally associated with flow behaviours in the partially filled channel. Interestingly, the foam microstructure not only blocks and traps the flowing particles, yet causing the breakage of particle clusters. These particles either disperse within the incoming flow or cause more depositions on the foam surfaces. The build-up deposits would increase the pressure drops, as expected, but the effects of pore density become insignificant over time.